Electric Field Driven Extraction of Inorganic Anions Across a Polymer Inclusion Membrane. Issue 8 (16th July 2013) - Schmidt‐Marzinkowski, Julia; See, Hong Heng; Hauser, Peter C.
Abstract The potential use of plasticized cellulose acetate membranes for electric field driven extraction and preconcentration of inorganic anions was studied. The extraction of highly lipophilic ions such as perchlorate is possible by employing a membrane without any ion carrier, while anions of low lipophilicity, such as phosphate, require a carrier. Best extraction efficiency could be obtained for a membrane of 20 µm thickness and an applied voltage of 200 V. In a flow‐through arrangement the preconcentration factor was inversely dependent on the flow rate but constant for different concentrations. The extraction of perchlorate down to 2 nM was demonstrated.